Determining the variables affecting the prices of animal products by the network analysis in Turkiye - Akin, Ahmet Cumhur; Polat, Murat; Mat, Burak; Cevrimli, Mustafa Bahadir; Arikan, Mehmet Saltuk; Ozel, Zeynep; Tekindal, Mustafa Agah (Ankara Univ, 2023)
Recently, Turkiye has seen significant increases in animal products and input prices. These recent increases in prices have made it even more important to examine the prices of animal products and their associated factors. This study aimed to reveal the pattern network structure and characteristics of the prices of animal products and related variables for the 2010-2020 period in Turkiye. For this aim, a network analysis covered the prices of animal products, input prices used in producing these foods, and some economic variables. The study results revealed that Producer Price Index (PPI) and Agricultural PPI are key variables that are highly active in the network and act as a bridge between other unconnected variables. In addition, the results of the analysis suggest that the overall network consists of highly correlated variables and that the PPI and Agricultural PPI are the two most important variables. As a result, the pattern network structure shows that economic variables have a high impact on the prices of animal products. The network structure visualizes Turkiye's import-substitution model in animal production and foreign dependency on feed inputs, and the market structure affected by high exchange rates. In addition, as can be understood from the positive connections between feed inputs, the pattern network of the variables affecting the prices of animal products is largely shaped by feed prices and the internal dynamics of economic variables.
Keywords: Animal products; Food prices; Livestock economics; Network analysis; Turkiye